Hubungan Kecemasan Komunikasi Antarbudaya dengan Komunikasi Terapeutik pada Perawat di Ruang Rawat Inap Rumah Sakit - Za'im, Putra Pramadita Fachruz; Purwandari, Retno; Nur, Kholid Rosyidi Muhammad (jitek, 2023)
Intercultural communication apprehension defined as fear or anxiety as a result of interactions with people from different cultural backgrounds. While therapeutic communication defined as communication carried out by nurses in communicating with clients to build interpersonal relationships. This research was conducted to determine the relationship between intercultural communication apprehension and therapeutic communication in hospital ward nurse. Correlational quantitative research design with a cross-sectional survey design approach used consisted of 98 nurse respondents determined through the total sampling technique. Personal Report of Intercultural Communication Appreciation (PRICA) questionnaire and the therapeutic communication questionnaire showed that intercultural communication apprehension level among nurses was mostly at moderate level with a total of 69 nurses (70.4%) while nurse therapeutic communication was mostly at good level with a total of 82 nurses (83.7%). The Kendall's Tau-B test showed that there was no significant relationship with a p value of 0.698. Communication anxiety level can be influenced by gender, and ethnocentrism. While therapeutic communication can be influenced by age, gender, culture and language, level of education, and length of work of nurses. Nurses' understanding regarding these factors is needed to avoid intercultural communication anxiety and to improve therapeutic communication that can affect the quality of health services.